Implementasi Manajemen Pemasaran Pendidikan dalam Meningkatkan Minat Peserta Didik Baru di MIS Pasirkiara - Siti Julaeha (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This research aims to evaluate the application of educational marketing management in increasing the interest of new students at MIS Pasirkiara. By referring to Henri Fayol's classic management theory, this research investigates how planning, organizing, directing, coordinating and controlling are applied in school marketing strategies. The method used in this research is descriptive qualitative, with data collection through observation, interviews and documentation. The research results show that MIS Pasirkiara has implemented marketing management principles in accordance with Fayol's theory, although there are several obstacles such as a lack of competent workforce in the marketing field. However, this school has advantages in superior programs such as qiroat, memorizing juz 30, and boarding school, as well as the leadership of the principal who is a public figure. These superior programs need to be evaluated in more depth to ensure their effectiveness in attracting new students and meeting the expectations and needs of prospective students. Promotion carried out through recitations and community activities has a positive impact in introducing the institution. However, this method still needs to be developed further in order to reach a wider audience and maximize the results of the promotions carried out. Increasing collaboration with local communities and other educational institutions to build a wider network and expand promotional reach. Regularly monitor the results of implemented marketing strategies and make adjustments based on data and feedback to ensure desired goals are achieved